2013
DOI: 10.1017/s1461145713001429
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone heat shock protein 70 in nucleus accumbens core: a novel biological target of behavioural sensitization to morphine in rats

Abstract: Drug addiction is a major public health issue, yet the underlying adaptation of neural networks by drugs of abuse is not fully understood. We have previously linked chaperone heat shock protein 70 (Hsp70) to drug-induced adaptations. Focusing on the NAc core and shell, the present study aims to provide further findings for our understanding of the relation between behavioural sensitization to morphine and Hsp70 at transcriptional and functional levels in rats. Firstly, we delineated the characteristics of beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
(97 reference statements)
2
13
0
Order By: Relevance
“…These gene expression changes could be related to opioid-induced temperature fluctuations in the nucleus accumbens (88), though they may also indicate a general response to cellular stress that is independent of temperature. Striatal expression of heat shock proteins is tied to psychomotor sensitization, withdrawal, and other behavioral responses to opioids (85,(89)(90)(91)(92)(93)(94), supporting functional relevance of the transcriptional changes we observe.…”
supporting
confidence: 71%
“…These gene expression changes could be related to opioid-induced temperature fluctuations in the nucleus accumbens (88), though they may also indicate a general response to cellular stress that is independent of temperature. Striatal expression of heat shock proteins is tied to psychomotor sensitization, withdrawal, and other behavioral responses to opioids (85,(89)(90)(91)(92)(93)(94), supporting functional relevance of the transcriptional changes we observe.…”
supporting
confidence: 71%
“…Previous studies suggested that HSP70 is a stress-inducible HSP that promotes survival and invasion of PCa, and inactivation of HSP70 leads to the loss of invasion in various cancer cell types. 24 Although the HSP70 inhibitor KNK437 produced no visible effects on the function of TXNDC5 overexpression in PCa cells ( Supplementary Figures 5a and b), silencing HSP70 ( Supplementary Figure 5c) or KNK437 treatment ( Supplementary Figures 5d and e), which has been shown to interfere with transcriptional activation of HSP70, 25 could decrease TXNDC5 protein expression through reducing the half-time of TNXDC5 protein ( Supplementary Figure 5f). Their interaction further supports the pro-metastasis function of TXNDC5.…”
Section: Discussionmentioning
confidence: 99%
“…The research reports a correlation between behavioral sensitization to morphine and Hsp70 as evidenced by Hsp70 inhibition of Hsp70. The study suggested that Hsp70 is a target for adaptations with relevance to addiction [11].…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 97%